Marriage Age Maturity for the Health and Future of Tlogosari Village Youth - Nanda Widaninggar; Muhammad Firdaus (TGO Journal of Community Development, 2023)
Tlogosari Village is located in Tlogosari District, Bondowoso Regency. The residents of Tlogosari Village generally have a livelihood in agriculture, both as farmers, farm labourers, as well as casual daily laborers and animal husbandry. The location of this village area is quite far from the city center of Bondowoso, but the level of facilities and business environment in this village is quite advanced, although it is overshadowed by early marriage. This, of course, stems from the low level of public understanding of the importance of maturing the age of marriage for the health and future of Tlogosari Village youth. This socialization was carried out by involving the Village Government, the Tlogosari Police, extension workers from the BKKBN, with the organizers being students participating in the STIE Mandala Real Work Lecture. The result was that the responses from the participants who came from junior and senior high school students around the Tlogosari District area were very enthusiastic and it turned out that the high rate of early marriage in this area was also due to encouragement from parents.